Macroscopic Responsive Liquid Quantum Dots Constructed via Pillar[5]arene‐Based Host‐Guest Interactions. Issue 39 (23rd August 2016) - Ma, Junkai; Shi, Fangdan; Tian, Demei; Li, Haibing
Abstract: Liquid quantum dots (QDs) have been used as a fluorescent films sensor. Constructing a macroscopic, responsive, liquid QD system for lysine (Lys) is a challenging task. To achieve a selective macroscopic response towards Lys, herein we present a new strategy for integrating host–guest chemistry into a liquid QD system. Water‐soluble pillar[5]arene WP5 was designed and synthesized as a host. WP5 was introduced onto the surface of PEG1810‐modified QDs by host–guest interactions to obtain liquid WP5‐1810‐QDs. The interaction between WP5 and Lys is stronger than that between WP5 and PEG‐1810, causing WP5 to be released from the 1810‐QDs surface in the presence of Lys, resulting in macroscopic fluorescence quenching. This smart material shows promise in amino acid sensing and separation. Abstract : Going dotty : Supramolecular liquid quantum dots (liquid WP5‐1810‐QDs) have been produced by the interactions between PEG‐1810 and water‐soluble pillar[5]arene (WP5). The proposed supramolecular QDs demonstrate a selective response toward lysine (see figure). In sharp contrast, the microstructure, fluorescence, and also fluidic temperature were evidently altered with lysine and other amino acids. It is anticipated that this study will pave a way for constructing smart sensors.